Regarding the Relationship Knowledge of Mother Nutrition and Parenting for Young Mothers with the Nutritional Status of Children Aged 12-24 Months - Nur Mei Sari; Esi Emilia Esi Emilia; Juliarti Juliarti; Erli Mutiara; Novita Sari Harahap (Universitas Pendidikan Indonesia (UPI), 2022)
One way to improve better and quality human resources is to pay attention to nutritional status starting from the First 1000 Days of Life in children, so that children's growth and development will also be optimal. The purpose of this study was to determine the relationship between maternal nutritional knowledge and parenting style of young mothers with the nutritional status of children under two. This type of research uses a cross-sectional design with a sample of 70 respondents taken by total-sampling technique. Data analysis was performed using descriptive tests, correlation tests, and multiple linear tests. The results showed that 54.2% had poor knowledge, 55.71% had poor parenting, and 35.71% had poor nutritional status.